The ox-bow incident - Clark, Walter van Tilburg 1909-1971 (Twenthieth Century Fox Home Entertainment, 2003)
A cowboy is unable to prevent three wandering travellers from being unjustly lynched for murder.
Orig.: USA, 1943. - Sprache: Engl., Span. - Untertitel: Engl., Span. - Enth. Bonusmaterial
Keywords: Lynching -- West (U.S.) -- Drama; Murder -- West (U.S.) -- Drama; Western -- Film; Film